State Institutional determinants for China’s intermediate goals: indigenous technology, development of industry, and internationalization of companies - Valdiglesias Oviedo, Jhon (2019)
This article analyzes the improvement of state institutional quality as a determinant of China’s economic success, achieved through the accomplishment of intermediate economic goals. Conventional wisdom that market forces are the sole determinant of liberalization cannot fully explain the Chinese economic boom. With the aim of catching up with developed countries, China has steadily enacted reforms, with slight emphasis on political reforms and continual, aggressive emphasis on concurrent economic ones. Through this combination of state designs and strategies, China has achieved the intermediate goals necessary to sustain the fast and stable rates of economic growth observed in recent decades. To analyze this process, this study will focus on the analysis of three approaches: (i) technological element; (ii) development of the auto industry, and (iii) internationalization of Chinese companies. The recent literature related to the institutional approach offers a proper theoretical framework to understand China’s recent economic development and the improvement of state institutional quality.